India's strategic culture: the making of national security policy - Shrikant Paranjpe (Routledge, 2013)
"This book argues that the Indian strategic worldview underpinning its national security policy is born out of a predominant historical-civilizational perspective. Based on an understanding of India as a 'civilization-state' with long history, this evolved strategic approach engages with security from a global point of view and not a national one that typically focuses on the survival of the nation-state. Guided by its cultural and civilizational ethos, this approach has helped define India's changing role in the post-colonial world order -- from maintaining its strategic autonomy and attending to its developmental needs in the Cold War era to adopting a measured, mature and assertive role in the international affairs of the post-Soviet era of globalization. Providing a nuanced and comprehensive understanding of India's strategic culture in terms of conceptual formulations in the West as well as its own distinct historic trajectory of evolution in the subcontinent, the book traces its origins and pivotal applications in changing security policy frameworks in the post-independence and post-liberalization international relations. Further, the author examines the role of India's strategic thinking in defining state's policy responses to internal conflicts along political, economic, religious, and ethnic lines. The volume also evaluates the prevailing debates on the legitimacy of situation-based use of force, the traditional peace approach and the revisionist position that India seeks to emphasize in the current unequal geopolitical order. It will especially interest scholars, teachers and students of defence and strategic studies, international relations, history, and political science."--Publisher's website.